Iliopectineal line: A valuable radiological reference for spino-pelvic parameters - Baco,Abdul M; Mukhter,Khalid; Moghamis,Isam; Mehrab,Nasser; Alhabash,Mohamed A; Abdalrahman,Mutaz A; Alhammoud,Abduljabbar (Journal of Musculoskeletal Surgery and Research)
Objectives: Spinopelvic parameters are crucial to address sagittal spinal imbalance; such measurements require standardized lateral radiographs that include spine and hips, which are neither always available, nor readily feasible intra-operatively. The aim of this study was to describe pelvic radiological reference points that could provide reliable sagittal balance estimates from conventional lumbosacral lateral radiographs. Methods: A descriptive, cross-sectional, radiological-based study was conducted. Readings were taken from institute’s digital radiology library, blinded to personal and clinical data. The correlation was made to conventional pelvic incidence (CPI), conventional pelvic tilt (CPT), and sacral slope (SS), measured for the same patients, and from the same standardized standing radiographs that included femoral heads. Results: Radiological images for 140 adult subjects, with suspected or established spine problems were studied. The average lumbar lordosis (LL) of 3 readers was 47 ± 13 (13–81) with an interclass agreement of 0.9, SS was 41 ± 9 with an interclass agreement of 0.9, CPI was 53 ± 10 with an interclass agreement of 0.8, CPT was 14 ± 8 with an interclass agreement of 0.9, iliopectineal inclination (IPI) of 4 readers was 64 ± 8 with an interclass agreement of 0.7 and iliopectineal tilt (IPT) was 24 ± 8 with an interclass agreement of 0.8 LL was with 6° of CPI and 16° of IPI. The CPI was equal to (CPI = SS + [CPT + 1.2]) and (IPI = SS + [IPT + 0.6]). The IPI was negatively correlated with CPI –0.2 P = 0.006, and IPI was negatively correlated with CPT –0.333 P < 0.001. Conclusion: Iliopectineal line provides reproducible readings, closer values to LL, and addresses the center of mass displacement.